2014
DOI: 10.1590/s0103-84782014000100025
|View full text |Cite
|
Sign up to set email alerts
|

Avian IgY antibodies: characteristics and applications in immunodiagnostic

Abstract: Immunoglobulin Y (IgY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 37 publications
1
29
0
3
Order By: Relevance
“…Currently, there are several methods to isolate and purify functional active chicken IgY from egg yolk, even for large scale purification (Munhoz et al, 2014). These methods can be performed by salt precipitation (Deignan et al, 2000;Chacana et al, 2003), chromatographic techniques (Meulenaer and Huyghebaert, 2001), and ultrafiltration (Kim and Nakai, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are several methods to isolate and purify functional active chicken IgY from egg yolk, even for large scale purification (Munhoz et al, 2014). These methods can be performed by salt precipitation (Deignan et al, 2000;Chacana et al, 2003), chromatographic techniques (Meulenaer and Huyghebaert, 2001), and ultrafiltration (Kim and Nakai, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…IgY technology has been used in many medical areas, especially for diagnosis purposes. Specific chicken antibodies have been successfully used against a wide variety of antigens (Munhoz et al, 2014). Various authors reported the efficiency, sensitivity, and specificity of diagnostic tests using IgY from various microorganisms such as Toxoplasma gondii, Schistosoma japonicum, Trichinella spiralis and coronavirus (Ferreira Júnior et al, 2012;Cai et al, 2012;Wang et al, 2012;Palaniyappan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both polyclonal and monoclonal antibodies may be good options in this regard. The polyclonal immunoglobulin yolk (IgY) antibodies produced in chicken laying eggs have various advantages, such as high affinity for detection, multiple epitope recognition [33], low cost, and ease in purification compared to blood collection [34]. On the other hand, monoclonal-derived antibodies are also good tools for detection because they demonstrate specific binding affinity to their targets (ZIKV_E proteins).…”
Section: Discussionmentioning
confidence: 99%
“…Here we applied the cathepsin F capture ELISA for coproantigen diagnosis of human opisthorchiasis. Making use of chicken IgY, which does not cross react with mammalian immunoglobulins [34,20] as a capture antibody for native cathepsin F in the feces and a rabbit anti- Opisthorchis somatic antigens as the second antibody, we observed sensitivity greater than 90%. Stability and proper binding of chicken IgY to ELISA plate are additional advantages of utilizing this antibody as a capture antibody [35].…”
Section: Discussionmentioning
confidence: 99%
“…Chicken IgY antibody, the major serum immunoglobulin in birds, has functions similar to mammalian IgG [20]. It is a stable immunoglobulin that can be simply obtained from egg yolk with high quantity with no necessity to bleed the laboratory animal.…”
Section: Introductionmentioning
confidence: 99%